An isotope dilution-liquid chromatography-tandem mass spectrometry (ID-LC-MS/MS)-based candidate reference measurement procedure (RMP) for the quantification of aldosterone in human serum and plasma - Taibon, Judith; Santner, Tobias; Singh, Neeraj; Ibrahim, Sara Cheikh; Babitzki, Galina; Koeppl, Daniel; Gaudl, Alexander; Geistanger, Andrea; Ceglarek, Uta; Rauh, Manfred; Geletneky, Christian (Clinical Chemistry and Laboratory Medicine, 2023)
Objectives: An isotope dilution-liquid chromatography-tandem mass spectrometry (ID-LC MS/MS)-based candidate reference measurement procedure (RMP) for aldosterone quantification in human serum and plasma is presented.Methods: The material used in this RMP was characterized by quantitative nuclear magnetic resonance (qNMR) to assure traceability to SI Units. For liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis a two-dimensional heart cut LC approach, in combination with an optimal supported liquid extraction protocol, was established for the accurate analysis of aldosterone in human serum and plasma in order to minimize matrix effects and avoid the co-elution of interferences. Assay validation was performed according to current guidelines. Selectivity and specificity were assessed using spiked serum; potential matrix effects were examined by a post column infusion experiment and the comparison of standard line slopes. An extensive protocol over 5 days was applied to determine precision, accuracy and trueness. Measurement uncertainty was evaluated according to the Guide to the Expression of Uncertainty in Measurement (GUM), for which three individual sample preparations were performed on at least two different days.Results: The RMP allowed aldosterone quantification within the range of 20-1,200 pg/mL without interference from structurally-related compounds and no evidence of matrix effects. Intermediate precision was =4.7% and repeatability was 2.8-3.7% for all analyte concentrations. The bias ranged between -2.2 and 0.5% for all levels and matrices. Total measurement uncertainties for target value assignment (n=6) were found to be =2.3%; expanded uncertainties were =4.6% (k=2) for all levels.Conclusions: The RMP showed high analytical performance for aldosterone quantification in human serum and plasma. The traceability to SI units was established by qNMR content determination of aldosterone, which was utilized for direct calibration of the RMP. Thus, this candidate RMP is suitable for routine assay standardization and evaluation of clinical samples.
CRIS-Team WoS Importer:2023-04-21